2001
DOI: 10.1038/sj.jim.7000112
|View full text |Cite
|
Sign up to set email alerts
|

Chromium accumulation by two Streptomyces spp. isolated from riverine sediments

Abstract: Strains designated R22 and R25, isolated from Salí River sediments, Argentina, were highly resistant to chromium. These strains were shown by 16S rRNA sequencing studies to be Streptomyces spp.; this affiliation was consistent with morphological and chemical characteristics. Growth of strains R22 and R25 in medium containing 100 mg l(-1) chromate was reduced by only 23% and 34%, respectively, compared with growth in medium without added chromium. Streptomyces sp. strains R22 and R25 both accumulated chromium w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…AB0 grown in a copper supplemented MM were taken. Aliquots were removed for whole cell copper sorption analyses by nitric acid digestion while the remaining cells were broken in a French pressure cell at 20,000 psi (1,38 × 10 5 KN m -2 ) for sub-fractional sorption studies by differential centrifugation as described previously [8]. Samples of each fraction were removed for copper analysis.…”
Section: Subcellular Fractioningmentioning
confidence: 99%
See 1 more Smart Citation
“…AB0 grown in a copper supplemented MM were taken. Aliquots were removed for whole cell copper sorption analyses by nitric acid digestion while the remaining cells were broken in a French pressure cell at 20,000 psi (1,38 × 10 5 KN m -2 ) for sub-fractional sorption studies by differential centrifugation as described previously [8]. Samples of each fraction were removed for copper analysis.…”
Section: Subcellular Fractioningmentioning
confidence: 99%
“…Among the most common histochemical techniques, the Timm's reagent histochemical treatment has proved to be the most sensitive procedure for diagnosis of copper accumulation in liver when compared to orcein and rhodanine methods [24]. On the other hand, subcellular fractioning is a very common and valid technique for detecting metal distribution within the cell as it has been successfully applied to prove Cr and Cd accumulation in Streptomyces, Pseudomonas stutzeri and Bacillus subtilis, respectively [8,25,26].…”
Section: Introduction *mentioning
confidence: 99%
“…The first report on Cr(VI) reduction by Streptomyces was by Das and Chandra [21]. Amoroso et al [22] reported on Cr(VI) bioaccumulation by Streptomyces strains, whereas Laxman and More [18] determined Cr(VI) reduction by Streptomyces griseus.…”
Section: Introduction *mentioning
confidence: 97%
“…The first report on Cr(VI) reduction by Streptomyces was documented by Das and Chandra (1990). Amoroso et al (2001), reported on Cr(VI) bioaccumulation by Streptomyces strains, whereas Laxman and More (2002) determined Cr(VI) reduction by Streptomyces griseus. Polti et al (2009), determined Cr(VI) reduction by Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%